Bob the builder: bob and the goalie (Egmont Great britain, 2012)
Bob the Builder and his crew are putting in a parking lot at the new Milkshake Bar. Scoop decides to experiment with the concrete mixture, but his experiment goes terribly wrong. Can Bob and the team help fix this big mix-up?